The Urgency of Instituting Systemic Cybersecurity Curriculum within STEM at Secondary Educational Levels in Preparation for Postsecondary Institutions. - Robert Spencer (Journal of Cybersecurity Education, Research & Practice, 2025)
Over the last 20 years, many secondary institutions have made advances developing curriculum defined as “STEM (Science, Engineering and Mathematics)” in order to ensure secondary students are eligible to apply as well excel in technology degree programs at the college and university levels. Although various initiatives exist, there are studies however, which allude to a great possibility that there will be a lack of cybersecurity professionals filling present day and anticipated future positions. Despite a large number of federal and educational enhancements there is need for additional research regarding instituting overall systemic processes and curriculum which supports secondary student transition into postsecondary degree programs in order to populate the future demand for cybersecurity specialists. There is need of additional research revealing secondary STEM inclusion of specifically focused cybersecurity curriculum in prepatory format allowing coordinated transition from secondary institutions cybersecurity programs. Using a literature review of multiple documents and studies, this article reveals challenges related to the history and status of cybersecurity curriculum included within STEM at secondary institutions. The documents revealed elements related to difficulties as well as successful endeavors experienced by faculty and administration regarding developing and institutionalizing cybersecurity curriculum within STEM. Linking secondary and postsecondary STEM curriculum may enhance the potential for developing technology professionals in the field of cybersecurity in the future. This article advocates formal institution of cybersecurity curriculum developments within STEM programs at the secondary educational levels supporting transition into postsecondary cybersecurity degree programs.